Akanthomyces neocoleopterorum, a new verticillium-like species - Chen, Wan-Hao; Han, Yan-Feng; Liang, Jian-Dong; Liang, Zong-Qi (Phytotaxa, 2020)
A new species, Akanthomyces neocoleopterorum, which was isolated from an infected ladybug, is introduced. Morphological comparisons with extant species and DNA-based phylogenies from analysis of a multigene dataset support the establishment of the new species. It differs from other species by having mononematous and verticillium-like conidiophores, longer phialides, and mostly cylindrical conidia. Both the morphological identification and phylogenetic analysis of combined ITS, LSU, RPB1, RPB2 and TEF sequence data support A. neocoleopterorum as a new species in the genus Akanthomyces.